Efficient adsorption of Europhtal onto activated carbon modified with ligands (1E, 2E)-1, 2-bis(pyridin-4-ylmethylene)hydrazine (M) and (1E, 2E)-1, 2-bis(pyridin-3-ylmethylene)hydrazine (SCH-4); response surface methodology. Issue 53 (11th June 2015) - Ghaedi, M.; Alam barakat, E.; Asfaram, A.; Mirtamizdoust, B.; Bazrafshan, A. A.; Hajati, S.
<x xml:space="preserve">Abstract</x> Porous activated carbon was modified with (1E, 2E)-1, 2-bis(pyridin-4-ylmethylene)hydrazine (M) and (1E, 2E)-1, 2-bis(pyridin-3-ylmethylene)hydrazine (SCH-4).